2002
DOI: 10.1002/app.11309
|View full text |Cite
|
Sign up to set email alerts
|

Polylactide/montmorillonite nanocomposites and microcomposites prepared by melt blending: Structure and some physical properties

Abstract: Polylactide (PLA)/clay nanocomposites loaded with 3 wt % organomodified montmorillonite and PLA/clay microcomposites containing 3 wt % sodium montmorillonite were prepared by melt blending. We investigated the morphology and thermal properties of the nanocomposites and microcomposites and compared them with unfilled PLA, keeping the same thermomechanical history. The influence of the processing temperature on the structural characteristics of the investigated systems was determined. The investigations were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
222
0
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 364 publications
(239 citation statements)
references
References 20 publications
14
222
0
3
Order By: Relevance
“…As expected there are no traces of PLA crystalline structure both for PLA ( Figure 2) and for PLA nanocomposites based on clay nanoparticles, as already reported in literature for PLA/organically modified montmorillonite nanocomposites [19,[26][27][28]. These observations are in perfect agreement with the previously published data [5,19,[27][28][29] on similar materials. The WAXS pattern of PLA is characterized by a broad band with maximum at 2" % 17º, indicating a completely amorphous structure (Figure 2).…”
Section: Results and Discussion 31 Morphologysupporting
confidence: 93%
“…As expected there are no traces of PLA crystalline structure both for PLA ( Figure 2) and for PLA nanocomposites based on clay nanoparticles, as already reported in literature for PLA/organically modified montmorillonite nanocomposites [19,[26][27][28]. These observations are in perfect agreement with the previously published data [5,19,[27][28][29] on similar materials. The WAXS pattern of PLA is characterized by a broad band with maximum at 2" % 17º, indicating a completely amorphous structure (Figure 2).…”
Section: Results and Discussion 31 Morphologysupporting
confidence: 93%
“…This could have been due to the PLA reacting readily with the starch matrix to form strong interactions between them. [38] Addition of different amounts of clay to the nanocomposites reduced the bulk compressibility significantly (P < 0.05). The 1, 3, and 5 wt % clay contents produced bulk compressibilities which were not significantly different from each other at 7.32, 5.87, and 7.39 MPa, respectively.…”
Section: Physical and Mechanical Properties Of Ts/pla/cloisite Na + Nmentioning
confidence: 96%
“…The variation of T g , by the incorporation of fillers is explained by a plasticizing effect of the PLA polymeric matrix by the organic filler [35,52]. Pluta et al [52], reported a T g reduction 54.1 °C to 53.2 °C with 3 wt% of montmorillonite. In the case of PLA-SC the difference among its composite is very slight (in 0.5 °C).…”
Section: Differential Scanning Calorimetry (Dsc) and Gel Permeation Cmentioning
confidence: 99%